BIOGRAPHIC VALUES OF H. ABDUL AZIS AS A SOURCE OF LEARNING IPS - muhammad ridha ilhami (JURNAL SOCIUS, 2021)
The purpose of the research is to explain the biography and describe the values of the biography of H. Abdul Azis. Next, describe the efforts to make the values of the biography of H. Abdul Azis as a source of social studies learning. The research uses historical methods, with heuristics, criticism, interpretation and historiography stages. Collecting oral sources, written sources and sources of past relics, then critiqued and interpreted to produce historical writings. The results showed that Abdul Aziz was born in Telaga Silaba Village, Hulu Sungai Utara, December 31, 1936. He graduated from SMPN Part A Amuntai, Hulu Sungai Utara (HSU). He served as Mantri Pamong in the 1950s, then Camat of Sungai Turak (1962), Panggang Lake (1965) and Paringin (1968). Head of the Regional Secretariat Government Division to the Chairman of the Regional Legislative Council II HSU (1968-1978). Barito Kuala Regent for two periods 1978-1983 and 1978-1983. Died in Banjarmasin, January 13, 1987. H. Abdul Azis had the values of discipline, hard work, responsibility and social care that supported him, so he was successful as a government official and managed to raise a family. The values from the biography of H. Abdul Azis can be used as a source of social studies learning by integrating them in the syllabus and lesson plans for IPS for SMP/MTs Class IX. The conclusion of the study is that from the biography of H. Abdul azis, there are four main biographical values, namely the value of discipline, hard work, responsibility and social care that can be used as sources for social studies learning.